(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article deals with the further improvement of the preschool education system, the introduction of modern educational programs and technologies in the educational process, the comprehensive intellectual, moral, aesthetic and physical development of children, the study of ways and methods of developing the cognitive activity of preschoolers.